2018
DOI: 10.3390/ijms19102914
|View full text |Cite
|
Sign up to set email alerts
|

Gummy Stem Blight Resistance in Melon: Inheritance Pattern and Development of Molecular Markers

Abstract: Gummy stem blight (GSB) causes enormous losses to melon (Cucumis melo L.) production worldwide. We aimed to develop useful molecular markers linked to GSB resistance. In this study, 168 F2 plants were obtained from the F1 population of a cross between the GSB-susceptible ‘Cornell ZPPM 339’ and the GSB-resistant ‘PI482399’ lines. A 3:1 ratio of susceptible and resistant genotypes was observed in the F2 population, indicating control by a single recessive gene. Nucleotide-binding site leucine-rich repeat (NBS-LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…In watermelon, six NBS-encoding R-genes were identified as candidates for gummy stem blight (GSB) resistance, which strongly supports our approach [75,76]. Finally, markers have been developed for detecting GSB resistance in melon based on the sequence polymorphism in the TIR-NBS-LRR gene MELO3C022157 [75]. All six candidate R-genes identified in the current study have corresponding homologues in watermelon and cucumber (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In watermelon, six NBS-encoding R-genes were identified as candidates for gummy stem blight (GSB) resistance, which strongly supports our approach [75,76]. Finally, markers have been developed for detecting GSB resistance in melon based on the sequence polymorphism in the TIR-NBS-LRR gene MELO3C022157 [75]. All six candidate R-genes identified in the current study have corresponding homologues in watermelon and cucumber (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…A study of the MLO (mildew resistance locus o) gene family in melon revealed candidate genes that might play roles in susceptibility to powdery mildew [74]. In watermelon, six NBS-encoding R-genes were identified as candidates for gummy stem blight (GSB) resistance, which strongly supports our approach [75,76]. Finally, markers have been developed for detecting GSB resistance in melon based on the sequence polymorphism in the TIR-NBS-LRR gene MELO3C022157 [75].…”
Section: Discussionmentioning
confidence: 56%
“…In watermelon, six NBS-encoding R-genes were identi ed as candidates for gummy stem blight (GSB) resistance [81,82]. Finally, markers have been developed for detecting both GSB and BFB resistance in melon based on the sequence polymorphism in the TIR-NBS-LRR gene MELO3C022157 [81,83]. Notably, all six candidate R-genes identi ed in the current study have corresponding homologues in watermelon and cucumber (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, a study of the MLO (mildew resistance locus o) gene family in melon revealed candidate genes that might play roles in susceptibility to powdery mildew [80]. In watermelon, six NBS-encoding R-genes were identi ed as candidates for gummy stem blight (GSB) resistance [81,82]. Finally, markers have been developed for detecting both GSB and BFB resistance in melon based on the sequence polymorphism in the TIR-NBS-LRR gene MELO3C022157 [81,83].…”
Section: Discussionmentioning
confidence: 99%
“…The disease severity of three individual leaves from each inoculated plant was scored 12 days after inoculation using a scale of 1 to 6 (Supplementary Figure S1) for ≥10%, 11-20%, 21-50%, 51-75%, 76-90% and >90% diseased/infected area per leaf, respectively [18]. Disease ratings were scored as per the methods described by Robin et al [36] and Hassan et al [37] with little modification. The percentage infected area (PIA) was measured as the ratio of infected area to total leaf area, multiplied by 100.…”
Section: Inoculation Sample Preparation and Assessment Of Bfb Resistmentioning
confidence: 99%